2003
DOI: 10.1016/j.jacc.2003.06.015
|View full text |Cite
|
Sign up to set email alerts
|

Phospholipid abnormalities in children with Barth syndrome

Abstract: Abnormal cardiolipin is a specific diagnostic marker of cardiomyopathies caused by TAZ mutations. These mutations lead to alterations in the fatty acid composition of several phospholipids, supporting the idea that TAZ encodes a human acyltransferase.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
181
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 188 publications
(190 citation statements)
references
References 25 publications
9
181
0
Order By: Relevance
“…The model is also applicable to heart, where we described complementary changes in PC and CL of two BTHS patients. 10 In these two patients, cardiac 16:0-18:2-PC increased at the expense of 16:0-20:4-PC. This, together with the lack of 18:2 in CL, suggested that 18:2 was transferred from PC to CL and 20:4 was used to reacylate lyso-PC ( Figure 6).…”
Section: Discussionmentioning
confidence: 76%
See 3 more Smart Citations
“…The model is also applicable to heart, where we described complementary changes in PC and CL of two BTHS patients. 10 In these two patients, cardiac 16:0-18:2-PC increased at the expense of 16:0-20:4-PC. This, together with the lack of 18:2 in CL, suggested that 18:2 was transferred from PC to CL and 20:4 was used to reacylate lyso-PC ( Figure 6).…”
Section: Discussionmentioning
confidence: 76%
“…10 Although the concentration of other phospholipids remained normal in BTHS, 10 it was not known whether or not the fatty acid composition of these phospholipids was affected as well. In the present study, we provided a comprehensive fatty acid analysis of PC, PE, and CL in lymphoblasts from BTHS patients and controls ( Table 1).…”
Section: Analysis Of Phospholipidsmentioning
confidence: 99%
See 2 more Smart Citations
“…BTHS is characterized by cardiac and skeletal myopathies and cyclic neutropenia (Barth et al, 1983(Barth et al, , 1999(Barth et al, , 2004; the disease presents in infants and if undiagnosed, is often fatal due to cardiac failure or sepsis. There are three hallmarks of the loss of Taz1p activity in the mitochondria of BTHS patients (Vreken et al, 2000;Valian-pour et al, 2002Valian-pour et al, , 2005Schlame et al, 2003;Schlame and Ren, 2006): 1) CL content is reduced; 2) CL contains more randomly distributed, saturated fatty acyl chains; and 3) there is an accumulation of monolysocardiolipin (MLCL). These three characteristics have been defined in the yeast Saccharomyces cerevisiae BTHS model (Vaz et al, 2003;Gu et al, 2004;Testet et al, 2005;Claypool et al, 2006); all but the accumulation of MLCL has been documented in the Drosophila melanogaster BTHS model (Xu et al, 2006a), and the mitochondrial phospholipids have not been characterized in the zebrafish BTHS model (Khuchua et al, 2006).…”
Section: Introductionmentioning
confidence: 99%